Blue Ocean Strategy di Industri Perhotelan - Kadek Linda Kusnita (Jurnal Manajemen dan Bisnis, 2019)
ABSTRACTThis research is intended to know the marketing carried out by Harper Kuta Hotel to get out of the Red Ocean Marketing carried out in the hospitality industry has implemented a red ocean zone which in all hotels uses the same marketing strategy, so marketing is offered in marketing. This study uses qualitative methods and uses four blue ocean frameworks that explain the strategies that must be corrected and corrected. Data collection uses interview techniques from each resource person. The final goal of this research is to learn the advantages possessed by Harper Kuta Hotel, so that they can choose the right strategy and have innovation.